2008
DOI: 10.17221/263-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge maps in agriculture and rural development

Abstract: rapid changes in the external environment require the decision-makers to select new approaches and methods of decision-making (Svoboda 2008). information and knowledge systems based on knowledge approach and or/MS methods have an important role in this process. Quality decision support systems and information and communication technologies and the quality of the provided information and knowledge for the decisionmakers are an important source of competitiveness (Šilerová, Kučírková 2008). This quality is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…They consider formulas as a special case of KG [38], because formulas satisfy the definition of KGs that represent the relationships and attributes of modeling systems [39]. Therefore, building KGs using formulas [40] could be a manner of semi-automatically developing and manipulating graphs, with mathematical semantics used to identify concepts within the graph [41].…”
Section: Kgs For Representing Mathematical Conceptsmentioning
confidence: 99%
“…They consider formulas as a special case of KG [38], because formulas satisfy the definition of KGs that represent the relationships and attributes of modeling systems [39]. Therefore, building KGs using formulas [40] could be a manner of semi-automatically developing and manipulating graphs, with mathematical semantics used to identify concepts within the graph [41].…”
Section: Kgs For Representing Mathematical Conceptsmentioning
confidence: 99%
“…Lange et al [10] suggested a multiontology-based foods-for-health knowledge system. Brožová et al [11] studied the optimization of agricultural production structure using knowledge graphs. Zheng et al [12] proposed an ontology-based system for agricultural knowledge management.…”
Section: Related Workmentioning
confidence: 99%
“…Znalostí mapy jsou děleny na tři základní typy (Gordon, 2000): myšlenkové mapy, koncepční mapy a kognitivní mapy. O využití znalostního mapování v agronomii se zmiňuje i zdroj (Brožová et al, 2008).…”
Section: Rešerše a Výzkumné Metodyunclassified